Theraplay: building healthy attachments - Rumley, Nancy A. (Kansas State University, 2008)
Theraplay is a technique used to replicate healthy parent-child interactions in order to build healthy attachments. Theraplay is a short-term therapeutic approach that is intimate, physical, personal and enjoyable. The goal of Theraplay is to improve attachments, self-esteem and trust in the relationship. The use of Theraplay has been shown to be beneficial for people of all ages including infants up to geriatric clients. This report offers an overview of Theraplay, provides clinical issues in which Theraplay can be implemented, describes the Theraplay process, and gives implications for further research. Because Theraplay is a highly specialized field, this report also gives information on how to become certified in Theraplay. This report was written for Masters' and Doctoral students in the mental health field that have an interest in working with clientele with attachment injuries.
Keywords: Theraplay; Attachment; Marriage and Family Therapy; Adoption; Foster; Therapy; Health Sciences, Mental Health (0347)